INNOVATIVE LANGUAGE LEARNING - Dewi, Kadek Yati Fitria (Universitas Panji Sakti, 2024)
AbstractTraditional teachings are often seen as practices that lead students to view language learning as a set of theories with less or no relevance to the real world. Teachers in traditional classrooms tend to pose children with many grammatical rules. As a result, children will only be able to memorize or master the rules of the target language, while they are less capable of applying what they learn in school to their daily lives. Therefore, educators now find it necessary to rethink how we teach language. This article discusses some innovative language teaching methods to help learners learn the target language as a holistic and contextual part.Keywords: innovative, language learning